An exploratory of incest among Malays in Malaysia: investigating intra-familial sexual abuse among inmates in two state prisons - Md. Noon, Hazizan; Khan, Rahmatullah; Abdul Karim , Noor Harun; Hassan, Mohd Kamal (IIUM Press, 2008)
This study is exploratory in nature. It is the first of its kind in Malaysia to examine the incest phenomenon from the perspective of those accused and convicted of incest. Previous studies in Malaysia had examined the phenomenon from the perspective of the victims and those involved in the treatment of the victims and family members. The study has the following research questions:(a) what demographic attributes are typically associated with those convicted of incest? (b) What circumstances (physical, social and psychological) facilitate or encourage the incestuous acts? (c)What explains sexual attraction to one's own family members? Forty-four inmates were interviewed using a structured interview questionnaire which attempted to elicit demographic, factual and behavioural data. Because the subjects for this study were sampled from two state prisons, the study lacks the generalizing power one normally expects of quantitative empirical research. The summarized findings revealed that 1) a majority of the subjects interviewed are from the lower income category (i.e., they were previously employed as drivers, guards, laborers and various other jobs which belonged to the 'industrial and manual group'), and do not possess education beyond that of completing primary schooling. 2) Out-of the forty four interviewed, twenty-two are the victim's natural parent, eleven are uncles, three are step-fathers, three are brothers and the other is grandfather, 3) Being alone with the victims, drunkenness, viewing pornographic videos/films, divorced from spouse and stress were the reasons and circumstances that trigger their sexual attraction towards the victims, and 4) 20 subjects said that they did not practice their religion faithfully. The number of subjects for this study was small; the findings are therefore tentative and cannot be generalized to a larger population. Research in greater depth is required in order to fully understand incestuous behaviour among Malaysians.